Structural and magnetic properties of lithium ferrite (LiFe5O8) thin films: Influence of substrate on the octahedral site order - BOYRAZ, CİHAT (AMER INST PHYSICS, 2011)
Structural properties of lithium ferrite [LiFe5O8, (LFO)] thin films are investigated as a function of substrate-induced strain and growth temperature. Through x-ray diffraction and Raman spectroscopy analysis we find LFO films grown on isostructural MgAl2O4 (MAO) are closer to bulk single crystal behavior, whereas the films remain coherently strained on lattice matched MgO substrate. Film texture and surface morphology are enhanced with better lattice match, indicating different growth modes on different substrates. Raman spectra reveal enhanced disorder of Li and Fe ions at the octahedral sites on MgO substrate contrasting with the relatively high degree of octahedral site ordering on MAO. (C) 2011 American Institute of Physics. [doi:10.1063/1.3533908]